AB0202 Cardiac Troponin T and Anti-Cardiac Troponin I Antibodies in Patients with Systemic Sclerosis: A Monocentric, Retrospective Pilot Study. (10th June 2014) - Vasile, M.; Kaya, Z.; Frerix, M.; Mueller-Ladner, U.; Rolf, A.; Meier, F.
Abstract : Background: Cardiac troponins (cTn) are widely used as biomarkers for the diagnosis and quantitation of cardiac injury (1). Autoantibodies against cTn, especially against cTnI (anti-cTnI), have been recently described in association with cardiac dysfunction (2). However, their clinical significance is still unclear. Systemic sclerosis (SSc) is a chronic autoimmune connective tissue disease that is associated with heart involvement, although often clinically occult (3, 4). Objectives: Hence, the value of elevated cTn levels and a possible autoimmune response against cTnI as biomarkers in patients with SSc were the aims of this study. Methods: Out of our monocentric SSc cohort we retrospectively identified 113 of 190 patients in whom routine laboratory assessment including high-sensitive cTnT was performed. Stored biosamples, available for 60/113 patients (53.1%), were used to assess auto-cTnI titres as previously described (5). A 2x2 table, using chi-square test, compared the results of cTnT and anti-cTnI. If available, cardiac magnetic-resonance-imaging (cMRI) data were retrospectively evaluated to assess early myocardial gadolinium enhancement (T1 ratio, as a marker for hyperemia and capillary leakage) as well as edema (T2 ratio). Results: Out of 113 patients with available results for cTNT, 41 patients (36.3%) had a positive and 72 (63.7%) a negative result. Biosamples were available for 21 cTNT positive and 39 cTNT negative patients. Anti-cTnI were detected in 17 samples (28.3%): in 8 (38.1%) cTNT positive compared to 9 (23.1%) cTNT negative patients (p=0.218). Anti-cTnI-titres were 1:40 in 7, 1:80 in 6 and 1:160 in 4 samples. cMRI data were available for three anti-cTnI positive patients (all diffuse cutaneous subtype). All of them had a distinct change in the T1 ratio (6.4-8.9), not in the T2 ratio. Late enhancement (gold standard for the detection of myocarditis) was present in one patient (6). Conclusions: The preliminary results of this pilot study suggest that cTnT levels are elevated in about one third of SSc patients, and anti-cTnI are present in about a third of cTNT positive patients. Additionally, anti-cTnI can be detected in about a quarter of cTNT negative patients. Whether cTNT and/or anti-cTnI autoantibodies might serve as new biomarkers in SSc heart disease need to be evaluated in further prospective trials. References: Kaya Z Clin. Immunol. 134, 80–88(2010). Kaya Z Circulation Research 110, 145–158(2012). Allanore Y Curr Opin Rheumatol 20, 697–702(2008). Meune C Arch Cardiovasc Dis 103, 46–52(2010). Leuschner F Eur. Heart J. 29, 1949–1955(2008). Desai CS Curr Opin Rheumatol 23, 545–554(2011). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3595